Competency frameworks in the Belgiam governments: causes, construction and contents - Brans, Marleen; Hondeghem, Annie (2005)
The Belgian Federal government and the Belgian Flemish government have picked up competency management as a multifaceted tool to suit their own visions of organizational change rather than simply responding to a new management trend in the private sector. Both governments have used it to foster both vertical and horizontal integration in their fragmented administrations, and to deal with problems of recruitment and retention to qualified personnel. The analysis presented here also reveals that the seemingly uniform use of `competency speak' hides multiple dimensions that provide several solutions to different organizational problems. At the same time, the cases examined demonstrate how the new tools both serve and dis-concert the diverse bureau-political interests of top civil servants, trade unions and Human Resource Management units. In addition, we examine how the new tools break with at least two traditional features of the highly formal and rigid career systems and the relatively low status of officials in the Belgian administrations. - Reproduced.
Keywords: Civil service